Influence of the Surface Topography of Titanium Dental Implants on the Behavior of Human Amniotic Stem Cells - Riedel, Rodrigo Nicolas (2024)
The dental implant surface plays a crucial role in osseointegration. The topography and physicochemical properties will affect the cellular functions. In this research, four distinct titanium surfaces have been studied: machined acting (MACH), acid etched (AE), grit blasting (GBLAST), and a combination of grit blasting and subsequent acid etching (GBLAST + AE). Human amniotic mesenchymal (hAMSCs) and epithelial stem cells (hAECs) isolated from the amniotic membrane have attractive stem-cell properties. They were cultured on titanium surfaces to analyze their impact on biological behavior. The surface roughness, microhardness, wettability, and surface energy were analyzed using interferometric microscopy, Vickers indentation, and drop-sessile techniques. The GBLAST and GBLAST + AE surfaces showed higher roughness, reduced hydrophilicity, and lower surface energy with significant differences. Increased microhardness values for GBLAST and GBLAST + AE implants were attributed to surface compression. Cell viability was higher for hAMSCs, particularly on GBLAST and GBLAST + AE surfaces. Alkaline phosphatase activity enhanced in hAMSCs cultured on GBLAST and GBLAST + AE surfaces, while hAECs showed no mineralization signals. Osteogenic gene expression was upregulated in hAMSCs on GBLAST surfaces. Moreover, α2 and β1 integrin expression enhanced in hAMSCs, suggesting a surface-integrin interaction. Consequently, hAMSCs would tend toward osteoblastic differentiation on grit-blasted surfaces conducive to osseointegration, a phenomenon not observed in hAECs.